2013
DOI: 10.1186/2045-9912-3-10
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of molecular hydrogen: a noteworthy potential therapy with clinical significance

Abstract: Studies on molecular hydrogen have evolved tremendously from its humble beginnings and have continued to change throughout the years. Hydrogen is extremely unique since it has the capability to act at the cellular level. Hydrogen is qualified to cross the blood brain barrier, to enter the mitochondria, and even has the ability to translocate to the nucleus under certain conditions. Once in these ideal locations of the cell, previous studies have shown that hydrogen exerts antioxidant, anti-apoptotic, anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 55 publications
1
94
0
2
Order By: Relevance
“…Cai et al, indicated that the apoptosis of neurons in newborn rats induced by hypoxia and ischemia is inhibited by inhalation of H2, as the ratio of Terminal-deoxynucleotidyl Transferase Mediated NickEnd Labeling (TUNEL) staining positive cells and the activity of caspase-3 and caspase-12 of the hippocampus and cortex was decreased (5) which was compatible with our finding about decrease of the activity of caspase-3 in hypothermic HRSS administrated groups. Also, studied showed that H2 can inhibit the TNF-α/NFκβ, Ras-ERK1/2-MEK1/2, and Akt/Gsk3b pathways which have been involved in apoptosis inflammatory responses, and gene regulation (10). So, further researches are required to clarify the exact mechanism and signaling pathway involved in the protective role of hydrogen in I/R injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al, indicated that the apoptosis of neurons in newborn rats induced by hypoxia and ischemia is inhibited by inhalation of H2, as the ratio of Terminal-deoxynucleotidyl Transferase Mediated NickEnd Labeling (TUNEL) staining positive cells and the activity of caspase-3 and caspase-12 of the hippocampus and cortex was decreased (5) which was compatible with our finding about decrease of the activity of caspase-3 in hypothermic HRSS administrated groups. Also, studied showed that H2 can inhibit the TNF-α/NFκβ, Ras-ERK1/2-MEK1/2, and Akt/Gsk3b pathways which have been involved in apoptosis inflammatory responses, and gene regulation (10). So, further researches are required to clarify the exact mechanism and signaling pathway involved in the protective role of hydrogen in I/R injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, these studies used different methods of hydrogen administration. A concentration of less than 4% by volume hydrogen gas in air is reported to be safe (5). The present study used a concentration of hydrogen were assessed before, and at 24 and 72 hours after treatment.…”
Section: █ Discussionmentioning
confidence: 99%
“…Recently, strong clinical and experimental evidence has shown that hydrogen, administered by gas inhalation or ingestion of an aqueous hydrogen-containing solution, has potent protective cellular effects in various diseases (4,5,10,20,21,24,26,27), but without major adverse effects (5). Previous studies have shown that hydrogen has antioxidant, anti-apoptotic, antiinflammatory, and cytoprotective properties that are beneficial to the cell (5).…”
Section: Increasing Evidence Suggests That Reactive Oxygen Speciesmentioning
confidence: 99%
See 2 more Smart Citations